2024
DOI: 10.2147/cmar.s444916
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Adverse Event-Related Adrenal Insufficiency Mediates Immune Checkpoint Inhibitors Efficacy in Cancer Treatment

Shasha Zhang,
Jianhua Wu,
Yue Zhao
et al.

Abstract: Purpose Immune checkpoint inhibitors (ICIs) have significantly improved the outcomes of patients with cancer; however, these agents may initiate immune-related adverse events (irAEs). Previous studies have demonstrated a robust correlation between disease prognosis and the occurrence of irAEs, specifically skin or endocrine irAEs. Herein, we aimed to evaluate the correlation between irAE-related adrenal insufficiency (AI) and ICI treatment efficacy. Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Such an integrated approach would allow us to balance the benefits of continued immunotherapy against the risks of serious irAEs, avoiding unnecessary cessation of treatment and suboptimal cancer control. Some studies even indicated that certain irAEs may be a good prognostic sign for ICI efficacy as they have been connected with increased progression-free survival and overall survival in certain situations [ 123 ]. To the authors’ best knowledge, there are currently no protocols that can be used for diagnosing irAE with PET; therefore, further research would be beneficial to create guidelines on interpreting FDG PET/CT results in the context of ICIs.…”
Section: Summary Future Perspectivesmentioning
confidence: 99%
“…Such an integrated approach would allow us to balance the benefits of continued immunotherapy against the risks of serious irAEs, avoiding unnecessary cessation of treatment and suboptimal cancer control. Some studies even indicated that certain irAEs may be a good prognostic sign for ICI efficacy as they have been connected with increased progression-free survival and overall survival in certain situations [ 123 ]. To the authors’ best knowledge, there are currently no protocols that can be used for diagnosing irAE with PET; therefore, further research would be beneficial to create guidelines on interpreting FDG PET/CT results in the context of ICIs.…”
Section: Summary Future Perspectivesmentioning
confidence: 99%